2021
DOI: 10.1186/s12906-021-03266-6
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthin cooperates with Granzyme B to restrain tumor formation in tongue squamous cell carcinoma

Abstract: Background Tongue squamous cell carcinoma (TSCC) is a common type of oral cancer, with a relatively poor prognosis and low post-treatment survival rate. Various strategies and novel drugs to treat TSCC are emerging and under investigation. Trichosanthin (TCS), extracted from the root tubers of Tian-Hua-Fen, has been found to have multiple biological and pharmacological functions, including inhibiting the growth of cancer cells. Granzyme B (GrzB) is a common toxic protein secreted by natural kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Sensitivities of 64% to 93% for presurgical magnetic resonance imaging (MRI) and of 66% to 85% for presurgical computed tomography (CT) have been reported in the detection of cervical lymph node metastasis [ 4 ]. Although, in a meta-analysis from Sun et al, 2022, better sensitivity and specificity was found for the MRI than the CT [ 5 ], other studies show similar sensitivity rates for both MRI and CT [ 6 ]. Relatively high sensitivity (75% to 90%) and specificity (94% to 99%) are reported in detecting lymph node metastases with 8F-fluorodeoxyglucose positron emission tomography (18FDG-PET) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivities of 64% to 93% for presurgical magnetic resonance imaging (MRI) and of 66% to 85% for presurgical computed tomography (CT) have been reported in the detection of cervical lymph node metastasis [ 4 ]. Although, in a meta-analysis from Sun et al, 2022, better sensitivity and specificity was found for the MRI than the CT [ 5 ], other studies show similar sensitivity rates for both MRI and CT [ 6 ]. Relatively high sensitivity (75% to 90%) and specificity (94% to 99%) are reported in detecting lymph node metastases with 8F-fluorodeoxyglucose positron emission tomography (18FDG-PET) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis and autophagy are common modes of tumor cell death [ 25 , 26 ]. It has been reported that TCS can promote the death of Oral squamous cell carcinoma SCC25 by inducing cell apoptosis [ 9 ]. In order to better understand the mechanisms of TCS-induced cell death, HCC cells were treated with 25 μg/mL TCS, total protein was extracted and the expression levels of apoptosis- and autophagy-related proteins were detected by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…TCS is the major active ingredient of Trichosanthes Kirilowii [ 36 ]. Previous studies reported TCS alone showed an excellent inhibitory effect on cancer cell proliferation in vitro [ 9 , 23 , 37 ]. However, TCS alone had not significantly inhibited tumor growth in immunodeficient nude mice in vivo [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astragalus Membranaceus (AM) and Radix Trichosanthis (RT) are two herbs widely used in TCM to treat different cancers, which have been proven to inhibit tumor growth and metastasis ( Zhu et al, 2021 ; Bian et al, 2022 ). Chinese herbal compound formula is used most commonly in the clinic, and it is more effective when certain specific herbs and certain ratios are used together.…”
Section: Introductionmentioning
confidence: 99%